Degree-Days: Growing, Heating, and Cooling - Clyde W. Fraisse; Silvana V. Paula-Moraes (EDIS)
How much and when it rains, freezes, and thaws can make the difference between boom and bust for a year's crop. However, temperature can predict more than boom or bust. Atmospheric temperature can predict the growth rates of many plants. For this reason, growers use a concept called growing degree-days (GDD), sometimes called heat units. This 5-page document discusses growing degree-days, use of the AgroClimate website to track and forecast GDD accumulation, heating and cooling degree-days, and methods for calculating HDD, CDD, and GDD. Written by Clyde W. Fraisse and Silvana V. Paula-Moraes, and published by the UF/IFAS Department of Agricultural and Biological Engineering, revised December 2010 and April 2018. http://edis.ifas.ufl.edu/ae428